2021
DOI: 10.1172/jci149125
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of SARS-CoV-2–specific CD4 response to COVID-19 severity and impact of HIV-1 and tuberculosis coinfection

Abstract: T cells are involved in control of coronavirus disease 2019 (COVID-19), but limited knowledge is available on the relationship between antigen-specific T cell response and disease severity. Here, we used flow cytometry to assess the magnitude, function, and phenotype of SARS coronavirus 2–specific (SARS-CoV-2–specific) CD4 + T cells in 95 hospitalized COVID-19 patients, 38 of them being HIV-1 and/or tuberculosis (TB) coinfected, and 38 non–COVID-19 patients. We showed that SARS-CoV-2–spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(135 citation statements)
references
References 72 publications
10
117
0
8
Order By: Relevance
“…This effect was more marked in the second wave group and may reflect some degree of immune regulation. During infection, SARS-CoV-2-specific CD4 T cells exhibit high expression of the activation marker PD-1 (Sattler et al, 2020;Riou et al 2021a), which may limit proliferative capacity in those with recent infection. There was a marked increase in the magnitude and proportion of CD8 responses to spike induced de novo after vaccination, compared to infection, with no difference between the three study groups.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was more marked in the second wave group and may reflect some degree of immune regulation. During infection, SARS-CoV-2-specific CD4 T cells exhibit high expression of the activation marker PD-1 (Sattler et al, 2020;Riou et al 2021a), which may limit proliferative capacity in those with recent infection. There was a marked increase in the magnitude and proportion of CD8 responses to spike induced de novo after vaccination, compared to infection, with no difference between the three study groups.…”
Section: Discussionmentioning
confidence: 99%
“…These data go in line with recent preliminary data suggesting that very rapid induction of CD8 + T cells could be a cause of asymptomatic disease [ 30 ]. A new study found that severe COVID-19 is not preferentially associated with the quantity of the CD4 + T cell response, but rather poor polyfunctionality and proliferative capacity, as well as enhanced immune activation [ 31 ]. An increased immune activation profile has been distinguished in numerous studies, and together with differential Th2, Th17 or Tfh responses to SARS-CoV-2 been associated with distinct disease outcomes [ 32 , 33 ].…”
Section: T Cell Responses In the Acute Phasementioning
confidence: 99%
“…The late detection of unsuspected tuberculosis in several otherwise typical COVID-19 patients is a cause for concern and increased clinical vigilance. We have documented here and elsewhere 42 that tuberculosis may adversely impact both antibody and T cell responses to SARS-CoV-2. Conversely, the immunological milieu set up in the lung by SARS-CoV-2, to which corticosteroid therapy will add, may have contributed to reactivation of subclinical or latent tuberculosis 44 .…”
Section: Discussionmentioning
confidence: 73%
“…We next determined relationships between disease severity amongst COVID-19 patients, the presence of HIV-1 and/or tuberculosis as co-morbidities, and the level of anti-SARS-CoV-2 nucleocapsid specific antibody levels determined by the Roche Elecsys assay 41 . We have previously reported increased antinucleocapsid antibody levels in COVID-19 patients with more severe disease although no overall association with survival was noted 42 . Although no significant quantitative difference in cut-off index was observed by HIV-1 and or tuberculosis status, 8/15 tuberculosis patients in total and 5/8 with HIV-1 and tuberculosis were below the threshold for positivity (Figure 4A).…”
Section: Sars-cov-2 Specific Antibody Responsementioning
confidence: 89%